A woman with dyspnea and recurrent pneumothorax: when dyspnea is not asthma. Issue 4 (3rd July 2020) - Chidharla, Anusha; Sehring, Matthew; Ascencio, Marisa Ayari; Chittivelu, Subramanyam
ABSTRACT: Lymphangioleiomyomatosis (LAM) is a rare disease characterized by cystic lung lesions, lymphatic abnormalities, and angiomyolipomas. It can take a significant amount of time to diagnose LAM due to the vague symptoms of fatigue, progressive dyspnea, pneumothorax, and pleural effusion. We present a case of a 29-year-old woman with recurrent spontaneous pneumothorax and progressive dyspnea who was initially misdiagnosed with asthma and was later found to have LAM. As with all rare diagnoses, there needs to be a suspicion of the disease in order for a further workup to be initiated. In patients with a compatible High-resolution CT scan of the chest, a high vascular endothelial growth factor-D (VEGF-D) value is diagnostic for LAM, and no other confirmatory test is needed.